Health Behavior of Young People Aged 12–18 with Autism Spectrum Disorder and Intellectual Disabilities in Hungary - Ágota Barabás; Renáta J. Erdei; Mariann Móré; Viktória Pázmány; Attila Sárváry; Emil Toldy-Schedel; Anita M. Grestyák; Attila Csaba Nagy; Orsolya P. Kiss; Péter Takács (Children)
Introduction: People with disabilities are characterized by suboptimal health and lower self-rating health. Their need for health care is greater, they often have a higher prevalence of health problems and they have more difficulty accessing health care. The aim of this study was to assess the health behaviors and health indicators of 12–18-year-old young people with intellectual disabilities and autism spectrum disorder, and to explore their school-related perceptions in the Northern Great Plain region of Hungary. Materials and Methods: A cross-sectional questionnaire survey was conducted with the participation of 185 young people. A custom questionnaire was used, based on the Health Behavior in School-aged Children (HBSC) survey, assessing eating habits, oral care, physical activity, mental well-being, and self-reported health status. The sample was categorized into three groups: the ID1 (Intellectual Disability level 1) group, encompassing young individuals with mild intellectual disability; the ID2 group, encompassing young people with moderate intellectual disability; and the ID+ASD group, encompassing young individuals affected by both intellectual disability and autism spectrum disorder. Results: Consumption of various food types was below optimal levels. Low intake of fruits and vegetables was common, with only 21.6% of the respondents consuming fruit daily and 23.8% consuming vegetables daily. ID1 group reported significantly higher rates of nervousness several times a week (17.8% vs. 5.6% and 6.9%, p < 0.001), sleep difficulties (28.8% vs. 7.4% and 15.5%, p = 0.032), and dizziness (9.6% vs. 1.9% and 3.4%, p = 0.022) compared to the other two groups. A third school-related factor, related to negative emotions, showed a near-significant difference (p = 0.064), suggesting that students with both autism spectrum disorder and intellectual disability perceive lower levels of acceptance from teachers. On school-free days, computer usage was significantly highest in the ID+ASD group; 50% of them used a computer for at least 4 h per day. Conclusions: To improve mental well-being among affected children, psychological support and the implementation of mental health programs are recommended. In addition to teaching stress management techniques and coping mechanisms, integrating relaxation techniques into comprehensive developmental programs—both individually and in groups—is advised. For teachers, it is recommended to acquire disability-specific communication strategies.